Numerical investigation of virtual control surfaces for aeroelastic control on compressor blades. (August 2018) - Motta, V.; Malzacher, L.; Peitsch, D.
Abstract: Virtual control surfaces are assessed numerically as a means to enhance the aeroelastic response of a compressor cascade. Virtual surfaces are realized with plasma actuators placed on the pressure and on the suction side of the blade trailing edge. The plasma-induced flow is meant to be against the direction of the freestream. This allows for generating controlled recirculating flow areas and in turn modifying the effective blade camber and enlarging the actual chord. Computational fluid dynamic analyses with the blades at constant angle of attack show that the effects of pressure side actuation on flow field, pressure distribution and integral loads are comparable to those of flap-like devices. On the contrary suction side actuation yields effects which are analogous to those of wing spoilers. Traveling wave simulations for the torsion mode show that properly triggering an alternate pressure/suction side actuation during the blade pitching cycle improves significantly the blade aeroelastic stability. At the same time an effective reduction in the peaks of the oscillating airloads normal to the freestream direction is achieved, with potential benefits for the alleviation of fatigue phenomena.